Marti, a man of science? - Roberto Sotolongo Echemendía (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
In general when the phrase ¨man of science¨ is heard, One immediately thinks of a physicist, a mathematician, a chemist, an astronomer, a biologist, etc., but very few imagine a scientist in a humanist, a philologist, a musicologist, much less in a politician. In this paper reflections are presented to answer the following question: was Martí a scientist? And arguments are offered, from different conceptual points of view, to demarcate Marti's life and work as a man of science.